Impact of the Lack of Diversity Within Surgery Career Pathways and Mitigating Factors. Issue 11 (November 2021) - Sutton, Erica; Montgomery Rice, Valerie
The lack of diversity in surgical career pathways impacts the cultural competence of the learning and working environment, the variety of leadership styles found within surgical leadership, and the ability of an organization to achieve equity in the workplace due to ongoing mistrust and untouched bias. Leading mitigating factors include developing pathways for greater numbers of diverse people at the high school and college level and implicit bias training. Though educators have had some success with these factors in the initial stages of diversifying early pathways, these factors are not yet correlated to entry into a surgical career. Future solutions to the lack of diversity in surgery will be predicated on surgeons collectively valuing justice, equity, diversity, and inclusion.